2013
DOI: 10.1002/hep.26567
|View full text |Cite
|
Sign up to set email alerts
|

Isolate-dependent use of claudins for cell entry by hepatitis C virus

Abstract: Hepatitis C Virus (HCV) entry involves at least four cellular factors, including CD81, the scavenger receptor class B type I (SCARB-1), occludin (OCLN), and claudin-1 (CLDN1). In addition, CLDN6 and CLDN9 have been shown to substitute for CLDN1 as HCV entry factors in human nonliver cells. We examined the role of different CLDN proteins during HCV entry by using cell lines expressing either predominantly CLDN1 (Huh-7.5) or CLDN6 (HuH6). Huh-7.5 cells were susceptible to all tested HCV isolates, whereas HuH6 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
62
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 56 publications
(64 citation statements)
references
References 14 publications
(24 reference statements)
1
62
1
Order By: Relevance
“…5C). Another study recently reported high levels of the main HCV entry factors but highly variable CLDN6 mRNA levels in liver biopsy specimens from HCV patients (17). Immunostaining of liver sections also demonstrated that, in contrast to CLDN6-positive seminoma, CLDN6 was not detected in human liver sections (Fig.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…5C). Another study recently reported high levels of the main HCV entry factors but highly variable CLDN6 mRNA levels in liver biopsy specimens from HCV patients (17). Immunostaining of liver sections also demonstrated that, in contrast to CLDN6-positive seminoma, CLDN6 was not detected in human liver sections (Fig.…”
mentioning
confidence: 76%
“…3 to 5). Interestingly, silencing of CLDN6 in Huh7.5 cells also did not affect HCV infection (17). Furthermore, these MAbs were unable to further decrease HCVpp entry into CLDN1-silenced Huh7.5.1 cells or when added simultaneously with the CLDN1-specific MAb to naive Huh7.5.1 cells, suggesting that CLDN6 and CLDN9 are not able to complement the absence of CLDN1 expression or blockage by the anti-CLDN1 MAb (Fig.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, the functional relevance of each of these factors for HCV infection of human liver cells is supported by ample experimental evidence from different laboratories (8). Interestingly, CLDN6 and CLDN9 were shown to functionally substitute for a lack of CLDN1 in human nonliver cells (9)(10)(11). Therefore, these factors together with either CLDN1, -6, or -9 apparently make up the minimal requirements to render cells permissive for HCV entry.…”
mentioning
confidence: 99%
“…Two other members of the CLDN protein family (CLDN-6 and CLD-9) could be used alternatively for cell entry by those viruses with broad CLDN tropism (Haid et al, 2014) and thus could be used as additional targets for therapy. However, while some strains efficiently use CLDN-6 as well as CLDN-1, some other strains, such as JFH-1 and J6, solely use CLDN-1 to access cells and this can explain the efficacy of the above-mentioned anti-CLDN-1 antibodies.…”
Section: Introductionmentioning
confidence: 99%